Pemberdayaan Remaja Karangtaruna Putus Sekolah Melalui Pelatihan Instalasi Listrik Dan Service AC - Roza, Indra; Nasution, Agus Almi; Siregar, Lisa Adriana (Jurnal TUNAS, 2019)
In Karangtaruna School Dropout Youth Training activities in Kotamatsum IV, Medan Area Medan City District has a very dense population, motivated by various tribes, different livelihoods and low parental education. As for the level of life there are still many who live below the average, with poor conditions, where parents are unable to pay for adolescents for school, causing many teenagers who drop out of school and unemployed .. With the Youth Training activities Karangtaruna teenagers dropping out will provide knowledge and ability in installing electricity and AC services to school dropouts from disadvantaged families, assisting the administration of Kotamatsum IV in realizing non-governmental organizations through Youth Organization, to provide skills, so that they have competence in finding work, or entrepreneurship in the field of installation. AC electricity and service.